IMPLEMENTASI BELAJAR MATEMATIKA MENYENANGKAN BERBASIS PEMBELAJARAN GAME INOVATIF DI MTS SARJI AR RASYID - Ida Fitriana Ambarsari; Nur Hasanah; Nur Azizah; Agusti Agusti; Indah Yana (JURNAL PENGABDIAN MANDIRI, 2022)
This community service activity in the form of implementing fun mathematics learning with innovative game-based learning to improve students’ motivation to learn mathematics, especially in comparison materials and to change students’ mindsets regarding learning mathematics. This community service activity was carried out in seventh grade in MTs Sarji Ar Rasyid. The innovative games implemented in this community service activity consist of two games with different goal but interrelated between one game and another. The method used in this community service activity is expository and the implementation of innovative games. Furthermore, the results of this community service activity can be seen from several discussions, namely, the achievement of the community service implementation, the achievement of the target number of service participants, the achievement of service goals, and the achievement of the understanding of the service participants towards innovative games and the ability to solve comparison problem.